Investigation of Observed Changes in Treated Hemp Hurds - Schwarzova, Ivana (GeoScience Engineering, 2016)
The effort to achieve sustainable development using renewable materials instead of limited ones is the current trend in the construction industry. Need for the development of environmentally friendly products is related to industrial interest in using of natural plant fibers as reinforcement in composites. Combination of organic filler and inorganic matrix creates high-quality products such as fiber boards and composites. Industrial hemp fibers are one of the mostly used natural fibers and due to their unique mechanical, thermal insulation, acoustic and antiseptic properties have great potential in composite materials. However, improving interfacial bonding between fibers and matrix is an important factor in fiber-reinforced composites. Optimizing the adhesion of fiber to inorganic matrix is related to the surface treatment processes. This paper deals with morphology characterization, study changes in chemical composition and structure of hemp fibers using by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) before and after physico - chemical treatment.